Building an analog-to-digital converter circuit - Ling, Yah Li (2008)
This research is to build and test an ADC circuit to convert the analog signals from anemometer into binary code for the computer. There are two major areas that need to be addressed which are hardware and software. The hardware consists of the parallel port, IC ADC such as ADC74LS93 and ADC74LS 195, and an anemometer as an analog signal source. The software we use is assembly language. The software programming enables computer collecting data. Data that collected in computer are more accurate than calculations which are doing by human. This can be substituted by human error. The ADC circuit can be test whether it is function normally or not depends on the pulses in the oscilloscope. The passive scope probe is put to the pin 2 and pin 7 of the comparator LM393 to confirm the waveform. The voltmeter is used to obtain the output voltages when the rotary potentiometer is adjusted to obtain the binary numbers from 00000000 (0) to 11111111 (256) by observed the LED. That means the output voltages is recorded from binary numbers 00000000 (0) to 11111111 (256). The values of the output voltages are important as it use to calculate the wind speed through computer. An ADC circuit is soldered in PBC and is combined to the anemometer and the computer for mapping. Through the research, we found that when the binary numbers or decimal values are increased; the output voltages are also increased. This can conclude that the decimal value is proportional to output voltage and the wind speed is also proportional to output voltage.